Late Developing Supernumerary Premolars: Reports of Two Cases - Soghra Yassaei; Mahdjoube Goldani Moghadam; S. M. Ali Tabatabaei (Case Reports in Dentistry)
This paper presents two cases of late developing supernumerary premolars. Case 1 is a female patient with nonsyndromic multiple supernumerary teeth located in the maxillary right premolar-molar region, maxillary left premolar region, and the mandibular right and left premolar regions. In this patient surgical removal of all supernumerary teeth was carried out to avoid complications during orthodontic treatment. Case 2 is a female aged 19 years in whom formation of a mandibular supernumerary premolar was observed which was not present at age 13. The patient was made aware of the supernumerary tooth presence, and periodic radiographic assessment was planned.